Evaluation of anthropometric characteristics of junior handball players in correlation with field testing - Muntianu Vlad-Alexandru; Voinea Nicolae-Lucian (ALTIUS ACADEMY Foundation - Faculty of Physical Education and Sports, 2020)
n the current context, due to the dynamics and speed with which the current handball game is developing,we can consider that all aspects of players' level of development can have an increased influence in the practice of this collective sport atincreased parameters that can bring individual player development, and the whole team.It is well known that the age of the juniors is a defining one for years to come in performance sport, so we consider it of greater importance to analyse their evolution. The purpose of the article is to highlight, in terms of anthropogenic characteristics, the differentiation within each post and how they are related to a set of specific field samples.